Minimal Hypersurfaces in Hyperbolic Spaces (Journal of Partial Differential Equations, 2020)
In this paper, we reprove a theorem of M. Anderson [Invent. Math., 69 (1982), pp. 477-494] which established the existence of a minimal hypersurface in the hyperbolic space with prescribed asymptotic boundary with non-negative mean curvature in the non-parametric case. We use the mean curvature flow method.
Keywords: Hyperbolic space; minimal hypersurfaces; mean curvature flow; comparison theorem